2000
DOI: 10.1021/la991519f
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin-Modified Gold Nanospheres

Abstract: A new procedure for the modification of gold nanospheres (2-7 nm diameter) with thiolated cyclodextrin receptors is described. The resulting monolayer-protected nanoparticles behave as multisite hosts in aqueous media, engaging in host-guest interactions with guest molecules in the solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
135
0
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 182 publications
(144 citation statements)
references
References 12 publications
6
135
0
3
Order By: Relevance
“…They have demonstrated that this system can be effectively adapted for colorimetric polynucleotide sequence assays [22]. We have shown that gold colloidal particles [23] and clusters [24] can be derivatized with thiolated cyclodextrins, which retain their molecular complexation properties on the surface of the nanoparticles. Rotello and coworkers have derivatized gold clusters with molecules terminated on hydrogen bonding residues and have demonstrated their binding to complementary solution partners [25].…”
Section: Nanoparticle-based Devicesmentioning
confidence: 99%
“…They have demonstrated that this system can be effectively adapted for colorimetric polynucleotide sequence assays [22]. We have shown that gold colloidal particles [23] and clusters [24] can be derivatized with thiolated cyclodextrins, which retain their molecular complexation properties on the surface of the nanoparticles. Rotello and coworkers have derivatized gold clusters with molecules terminated on hydrogen bonding residues and have demonstrated their binding to complementary solution partners [25].…”
Section: Nanoparticle-based Devicesmentioning
confidence: 99%
“…[24][25][26] The catalytic activities of some water-soluble metal nanoparticles modified with covalently attached CD receptors can be modulated by the inclusion interaction between organometallic compounds and CD, thus catalytic reactions can be carried out effectively. [25,27] Matt and coworkers successfully modified CDs as ligands to form chelate complexes of CD derivatives and transition-metal ions. [8] In recent years, ionic liquids (ILs), which consist of organic cations and appropriate anions, have received much attention due to their potential as a green and recyclable alternative to traditional organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, β-CD covered AuNPs were synthesized (see the supporting information (SI) available at stacks.iop.org/Nano/ 24/495103/mmedia) [28][29][30][31][32][33]. The resultant particles showed good water solubility and were found to be stable in water for a month.…”
Section: Resultsmentioning
confidence: 99%